POWTOON APPLICATION: ITS EFFECT ON STUDENTS’ LISTENING COMPREHENSION - Zulfia Siskawati; Nenri Suci Rahmadani (Universitas Muhammadiyah Metro, 2022)
The purpose of this research was to investigate the effect of using Powtoon Application on Students’ Listening Comprehension. The research design was pre-experimental research. The population was the eleventh grade students at MA As-SyuhadaDuri XIII. In order to take the sample, total sampling was used. 19 students of the eleventh grade of MA As-SyuhadaDuri XIII were as samples. Listening test was administered for them to collect data of their Listening Comprehension. Then, the data were analyzed by using Paired Sample T-test. Based on the score gathered, it showed that tcount was lower than ttable. The finding of tcount was -5.718 while the level of significance of 5% : 2=2,5%=0,025 sig. (2 tailed ) was 2.060. It showed that -5.718 < 2.060 or tcount<ttable. It indicated Ha was accepted and Ho was rejected. Thus, it could be concluded that the use of Powtoon Application had a significant effect on students’ listening comprehension at the eleventh grade students of MA As-SyuhadaDuri XIII.